A boy and a jaguar - Rabinowitz, Alan, 1953-; e; Houghton Mifflin Harcourt Publishing Company (Boston : Houghton Mifflin Harcourt, 2014)
The renowned cat conservationist reflects on his early childhood struggles with a speech disorder, describing how he only spoke fluently when he was communicating with animals and how he resolved at a young age to find his voice to be their advocate.
Accelerated Reader
Schneider Family Book Award Winner, ages 0-10 (2015)
Keywords: Rabinowitz, Alan, -- 1953-2018 -- Juvenile literature; Wildlife conservationists -- United States -- Biography -- Juvenile literature; Panthera -- Conservation -- Juvenile literature; Stuttering in children -- Juvenile literature; Human-animal communication -- Juvenile literature; Boys -- Juvenile literature; Jaguar -- Juvenile literature; Rain forests -- Juvenile fiction; Rabinowitz, Alan, -- 1953-; Wildlife conservationists; Panthera; Cats; Stuttering; Human-animal communication; Schneider Family Book Award: Winner -- 2015; Dust jackets (Bindings) -- 2014.